Medical biochemistry at a glance - Salway, J. G. (At a glance series (Oxford, England), 2012)
Medical Biochemistry at a Glance is a concise, illustrated summary of biochemistry and its relevance to clinical medicine. It is intended for students of medicine and the biomedical sciences such as nutrition, biochemistry, sports science, medical laboratory sciences, physiotherapy, pharmacy, physiology, pharmacology and veterinary science